Impact of the Choice of Diagnostic Criteria and Growth Reference on the Prevalence of Extrauterine Growth Restriction in Extremely-Low-Birthweight Infants - Clara González López; Gonzalo Solís Sánchez; Belén Fernández Colomer; Laura Mantecón Fernández; Sonia Lareu Vidal; Sara Fernández Castiñeira; Ana Rubio Granda; Alicia Pérez Pérez; Marta Suárez Rodríguez (MDPI AG, 2024)
Background and objectives: Variable diagnostic criteria and growth charts have been used for extrauterine growth restriction (EUGR). The objective was to assess the prevalence and concordance of EUGR in extremely-low-birthweight (ELBW) infants with the most frequent diagnostic criteria and growth charts. Materials and methods: An observational, retrospective and multicenter study was conducted from 2011 to 2020 including ELBW infants from the Spanish SEN1500 Network. EUGR prevalence was calculated at discharge using different definitions: cross-sectional (anthropometry less than the 10th centile), longitudinal (decrease of more than 1 SD from birth to discharge), "true" cross-sectional and "true" longitudinal (using the criteria previously described, excluding infants small for gestational age at birth). Concordance among Fenton, Olsen and INTERGROWTH-21st was assessed with Fleiss' Kappa coefficient. Results: The prevalence of EUGR was variable with the different definitions and growth references studied in the 7914 ELBW infants included. Overall, it was higher with Fenton for all the EUGR criteria studied by weight and length. The agreement among growth charts was substantial (κ > 0.6) for all the definitions except for longitudinal EUGR by weight (moderate, κ = 0.578). Conclusions: The prevalence of EUGR was variable in our cohort with the different diagnostic criteria and growth charts. The agreement among charts was good for all the definitions of EUGR except longitudinal EUGR by weight.